The Photoinduced Electrocyclization Reaction of Triphenylamine (TPA) in Sustainable and Confined Micellar Solutions: A Steady‐State and Laser Flash Photolysis Approach. Issue 4 (5th January 2022) - Sanmartín, Rocío A.; Salum, María L.; Protti, Stefano; Mella, Mariella; Bonesi, Sergio M.
Abstract: The irradiation of triphenylamine (TPA) under homogeneous (cyclohexane, acetonitrile and methanol) and micellar [sodium dodecyl sulfate (SDS), cetyltrimethylammonium chloride (CTAC) and polyethylene glycol monododecyl ether (Brij‐P35)] conditions has been investigated through a combined steady‐state and time‐resolved spectroscopic approach. Photolysis of TPA at 254 nm in different media afforded N ‐phenylcarbazole (N−PhCA) as the main photoproduct, and when the photoreaction of TPA was carried out in micellar solution the relative rate of formation of N−PhCA was found to be faster than in homogeneous media due to the environmental confined and hydrophobic micellar core. On the other hand, the transient N ‐phenyl‐ 4a, 4b ‐dihydrocarbazole (DHC0 ) was detected and fully characterized via laser flash photolysis. Finally, the location of TPA within the hydrophobic core of the micelle was investigated by 1D and 2D NMR spectroscopic analyses. Abstract : The photochemical behavior of triphenylamine (TPA) in homogeneous and micro‐heterogeneous media has been investigated combining steady‐state and time‐resolved spectroscopic approaches. Photolysis of TPA afforded N ‐phenylcarbazole and its formation was noticeably accelerated in micellar solution. Laser flash photolysis studies provided intermediate N ‐phenyl‐ 4a, 4b ‐tetrahydrocarbazole, with the reactivity of this compound depending on the media and atmospheres used. NOESY experiments localized TPA within the micellar hydrophobic core.